αvβ6 integrin may be a potential prognostic biomarker in interstitial lung disease - Saini, Gauri; Porte, Joanne; Weinreb, Paul H; Violette, Sheila M; Wallace, William A; McKeever, Tricia M.; Jenkins, Gisli (European Respiratory Society, 2015)
Idiopathic pulmonary fibrosis (IPF) and fibrotic nonspecific interstitial pneumonitis are progressive interstitial lung diseases (ILDs) with limited treatment options and poor survival. However, the rate of disease progression is variable, implying there may be different endotypes of disease. We hypothesised that immunophenotyping biopsies from ILD patients might reveal distinct endotypes of progressive fibrotic disease, which may facilitate stratification when undertaking clinical trials of novel therapies for IPF.43 paraffin-embedded, formalin-fixed lung tissue sections were immunostained for five molecules implicated in the pathogenesis of the fibrosis: α-smooth muscle actin (αSMA), αvβ6 integrin, pro-surfactant protein C (SP-C), hepatocyte growth factor (HGF) and tenascin-C (TenC). Levels of immunostaining and numbers of fibroblastic foci were quantified using operator-dependent and -independent methods. The relationship of all these markers to overall survival was analysed.Staining revealed high levels of αSMA, αvβ6 integrin, pro-SP-C, HGF and TenC, and fibroblastic foci. Immunostaining varied across samples for all molecules but only the extent of αvβ6 integrin immunostaining was associated with increased mortality. There was no association with the other markers measured.Our data suggest high levels of αvβ6 integrin may identify a specific endotype of progressive fibrotic lung disease.